2012
DOI: 10.1183/09031936.00213911
|View full text |Cite
|
Sign up to set email alerts
|

Riociguat for interstitial lung disease and pulmonary hypertension: a pilot trial

Abstract: We assessed the safety, tolerability and preliminary efficacy of riociguat, a soluble guanylate cyclase stimulator, in patients with pulmonary hypertension associated with interstitial lung disease (PH-ILD).In this open-label, uncontrolled pilot trial, patients received oral riociguat (1.0-2.5 mg three times daily) for 12 weeks (n522), followed by an ongoing long-term extension (interim analysis at 12 months) in those eligible (n515). Primary end-points were safety and tolerability. Secondary end-points includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 31 publications
1
106
0
7
Order By: Relevance
“…The safety, tolerability and preliminary efficacy of riociguat (a soluble guanylate cyclase stimulator) has been evaluated in an open-label, uncontrolled pilot trial in patients with PH and ILDs with some positive results. Riociguat was well tolerated and was associated with an increase in cardiac output and decrease in PVR at RHC evaluation after 12 weeks of treatment; mean PAP was unchanged [47]. Riociguat shows the potential to improve exercise capacity in some patients (evaluated using 6MWT distance) [47].…”
Section: Treatmentmentioning
confidence: 99%
“…The safety, tolerability and preliminary efficacy of riociguat (a soluble guanylate cyclase stimulator) has been evaluated in an open-label, uncontrolled pilot trial in patients with PH and ILDs with some positive results. Riociguat was well tolerated and was associated with an increase in cardiac output and decrease in PVR at RHC evaluation after 12 weeks of treatment; mean PAP was unchanged [47]. Riociguat shows the potential to improve exercise capacity in some patients (evaluated using 6MWT distance) [47].…”
Section: Treatmentmentioning
confidence: 99%
“…5 inhibitors) in appropriately designed trials are also necessary to study the effect of these drugs in these patients [18,39,40]. It is important to point out, however, that the presence of emphysema and abnormal pulmonary pathology in patients with CPFE and pulmonary hypertension may be associated with an imbalance in the ventilation/perfusion ratio (V9/Q9), as hypoxic vasoconstriction is one of the main mechanisms to avoid worsening arterial oxygenation.…”
Section: Review: Emphysema In Pulmonary Fibrosis V Cottinmentioning
confidence: 99%
“…It is important to point out, however, that the presence of emphysema and abnormal pulmonary pathology in patients with CPFE and pulmonary hypertension may be associated with an imbalance in the ventilation/perfusion ratio (V9/Q9), as hypoxic vasoconstriction is one of the main mechanisms to avoid worsening arterial oxygenation. Vasodilator drugs can worsen hypoxaemia by inhibiting this mechanism [39][40][41].…”
Section: Review: Emphysema In Pulmonary Fibrosis V Cottinmentioning
confidence: 99%
“…Hoeper et al reported the decrease of SaO 2 by 1−2% from baseline in the patients with PH (mPAP > 30 mm Hg) in the course of DPLDs treated with Riociguat in the observational study [64]. Nevertheless, mixed venous oxygen saturation slightly increased.…”
Section: Treatment Considerations Of Ph In the Course Of Dpldsmentioning
confidence: 99%